2013
DOI: 10.1016/j.jadohealth.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acute Sleep Restriction on Adolescents' Pedestrian Safety in a Virtual Environment

Abstract: Purpose Over 8,000 American adolescents ages 14-15 require medical attention due to pedestrian injury annually. Cognitive factors contributing to pedestrian safety include reaction time, impulsivity, risk-taking, attention, and decision-making. These characteristics are also influenced by sleep restriction. Experts recommend adolescents obtain 8.5 hours of uninterrupted sleep each night, but most American adolescents do not. Inadequate sleep may place adolescents at risk for pedestrian injury. Method Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 41 publications
5
44
2
2
Order By: Relevance
“…Inter-reviewer agreement for inclusion was good (Kappa coefficient = 0.65). Final selection included a total of 13 studies [12,13,[40][41][42][43][44][45][46][47][48][49][50]. All studies were published in English language.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inter-reviewer agreement for inclusion was good (Kappa coefficient = 0.65). Final selection included a total of 13 studies [12,13,[40][41][42][43][44][45][46][47][48][49][50]. All studies were published in English language.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the studies included participants aged from 6 to 16 years. The age ranges in seven studies were from 11 to 16 years [40][41][42][43]45,48]. Males and females were equally represented in all samples.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Three VR studies were identified regarding sleep disorders. Targeted disorders included: Acute sleep restrictions in adolescent teens [73], obstructive sleep apnoea syndrome in children [74], and narcolepsy or idiopathic hypersomnia in children [75]. While sleep disorders can affect well-being this was not the concern of each study.…”
Section: Sleep Disordersmentioning
confidence: 99%
“…In fact, some of the world's most devastating disasters have been the result of sleep loss (Colten & Altevogt, 2006). Several studies have linked insufficient sleep in older adolescents and young adults to safety hazards such as pedestrian accidents (Davis, Avis & Schwebel, 2013), motor vehicle accident (Pizza et al, 2010), workplace and home accidents (Dahl & Lewin, 2002), as well as school violence-related behaviors (Hildenbrand, Daly, Nicholls, Brooks-Holliday, & Kloss, 2013).…”
Section: Safety Consequences Of Sleep Insufficiencymentioning
confidence: 99%